2021
DOI: 10.1055/s-0041-1730363
|View full text |Cite
|
Sign up to set email alerts
|

Associations of the Neighborhood Built Environment with Gestational Weight Gain

Abstract: Objective This study aimed to determine whether specific factors of the built environment related to physical activity and diet are associated with inadequate and excessive gestational weight gain (GWG). Study Design This analysis is based on data from the Nulliparous Pregnancy Outcomes Study: Monitoring Mothers-To-Be, a prospective cohort of nulliparous women who were followed from the beginning of their pregnancies through delivery. At each study visit, home addresses were recorded and geocoded. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Among nulliparous pregnant individuals, Grobman et al found an association between multiple aspects of the built environment, including number of gyms, parks, and grocery stores, and less gestational weight gain. 7 These findings reinforce emerging data that highlight the relationship between community-level social vulnerability to adverse perinatal outcomes. 39 In the case of diabetes in pregnancy, glycemic control requires a multimodal approach, inclusive of pharmacotherapy, frequent blood glucose checks to titrate medication, and behavioral changes inclusive of diet and exercise.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Among nulliparous pregnant individuals, Grobman et al found an association between multiple aspects of the built environment, including number of gyms, parks, and grocery stores, and less gestational weight gain. 7 These findings reinforce emerging data that highlight the relationship between community-level social vulnerability to adverse perinatal outcomes. 39 In the case of diabetes in pregnancy, glycemic control requires a multimodal approach, inclusive of pharmacotherapy, frequent blood glucose checks to titrate medication, and behavioral changes inclusive of diet and exercise.…”
Section: Discussionsupporting
confidence: 72%
“…1–3 Diabetes and its risk factors disproportionately affect individuals who identify as racial or ethnic minorities and as low-income. 4,5 Social determinants of health experienced by these groups include both individual- and community-level factors, such as residence in a low-income neighborhoods, 6 built environment with less access to engage in physical activity, 7 unstable housing, 8 food insecurity, 9 lack of quality health care, 10 and experiences of systematic racism. 11 Glycemic control, which can be measured using glycosylated hemoglobin A 1c (Hb A 1c ), is affected by social determinants of health.…”
mentioning
confidence: 99%